Analýza fragmentů volné fetální DNA v plazme tehotných zen v průbehu tehotenství - Vodicka, R; Böhmová, J; Dhaifalah, I; Blumenthalová, J; Kratochvílová, R; Santavý, J; Procházka, M; Vrtĕl, R (Ceska gynekologie, 2010)
AIM OF STUDY: To assess cell free fetal DNA (cffDNA) fragmentation rate in pregnant women during the course of gravidity. STUDY DESIGN: QF PCR efficiency in cffDNA and quantitative analyses in particular cffDNA molecular size fractions. SETTING: The study was performed at Department of Medical Genetics and Fetal Medicine, University Hospital Olomouc. METHOD: 1. 363 plasma DNA samples from women in different week of pregnancy (from 4th w.g. to 37th w.g.) were tested for QF PCR efficiency in particular STRs and AMELX/Y. 2. Size fractionated cff DNA (150-300 bp, 300-500 bp, 500-760 bp) was quantified by QF PCR in 91 pregnant women (from 9th w.g. to 40th w.g.). 3. Size fractionated cff DNA from male fetuses was quantified by real time PCR (SRY/internal control) in 22 pregnant women (from 9th w.g. to 36th w.g.). RESULTS: 1. QF PCR efficiency decreased from longer to shorter molecules. 2. The only 500 -760 bp fraction showed cffDNA increase in relation to week of gravidity. 3. Indirect relation between amount of cffDNA and week of gravidity was found in 150-300 bp fraction by Real-time PCR. CONCLUSION: Assembling of all 3 approaches indicates increase of longer cffDNA molecules during the gravidity while level of the short cffDNA molecule fragments probably remains from the approximately 9th w.g. the same.
Keywords: plod; Female; Chromosomes, Human, Y; Electrophoresis, Capillary; lidský chromozom Y; polymerázová řetězová reakce; Polymerase Chain Reaction; elektroforéza kapilární; DNA Fragmentation; ženské pohlaví; fragmentace DNA; DNA; lidé; Fetus; těhotenství; Male; lidské chromozomy X; Chromosomes, Human, X; Microsatellite Repeats; mužské pohlaví; Pregnancy; mikrosatelitní repetice; Humans